BAHASA ARAB DAN FILOSOFI PEMBELAJARANNYA PADA PONDOK PESANTREN AS’ADIYAH SENGKANG: PERSPEKTIF FILSAFAT PROGRESIVISME - Sy, Ahmad Imran (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2020)
Pondok Pesantren As'adiyah Sengkang is one of the oldest Islamic boarding schools in South Sulawesi which continues to strive to develop the quality of learning Arabic in it. This effort is realized by continuing to develop approaches, methods, and contemporary Arabic learning techniques which are fundamentally different from what has been applied in Arabic learning activities that are consistent with the tradition of learning Arabic based on text analysis. In its philosophical framework, this phenomenon is one of the learning paradigms adopted by the progressivism philosophy which is oriented towards constructive innovation in order to achieve the maximum development of the quality of Arabic learning both on the ontological, epistemological, or axiological scale. One of the practical implications of this effort is the increasingly active students in Arabic learning activities because they get wider access to innovate in their position as learning subjects.